Philosophy of Nemui Nyimah as an Indonesian pedagogic value of theology for disability - Wiryadinata, Halim (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
This study aims to carry the local philosophical value of Indonesian culture, Nemui Nyimah, as the value of theology for disability. Religious institutions’ inability to provide hospitality for people with disabilities creates a social gap in society. The incapability of religious institutions is due to psychological and economic aspects. This situation makes it a heavy burden for religious institutions to increase the well-being of those with disabilities and to provide facilities for them. As a society leaves the job of accepting disabilities at the religious institution’s door, it constructs the inability of it. Through the sociology of religion approach, this research brings up the emic perspective of the problem. The core problem is analyzed and presented logically and systematically through critical thinking by assessing the literature. The result of this study is to convey the local culture, Nemui Nyimah, as a theological value of life, solidarity, hope, hospitality, and economic justice for disability. The conclusion is that the culture of Nemui Nyimah constructs theology for disability through the cosmological value of accepting with the open arms of a church as Christ accepts the failures.